Intelligent Evolutionary Optimization - Xu, Hua; Yuan, Yuan (Amsterdam : Elsevier, 2024)
Intelligent Evolutionary Optimization introduces biologically-inspired intelligent optimization algorithms to address complex optimization problems and provide practical solutions for tackling combinatorial optimization problems. The book explores efficient search and optimization methods in high-dimensional spaces, particularly for high-dimensional multi-objective optimization problems, offering practical guidance and effective solutions across various domains. Providing practical solutions, methods, and tools to tackle complex optimization problems and enhance modern optimization techniques, this book will be a valuable resource for professionals seeking to enhance their understanding and proficiency in intelligent evolutionary optimization.
Includes appendix and index
Keywords: Machine learning; Computational intelligence; Multi-objective optimization; Search algorithms